2019
DOI: 10.3390/molecules24071366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbazole Derivatives on Neurite Outgrowth and Hydrogen Peroxide-Induced Cytotoxicity in Neuro2a Cells

Abstract: Many studies have demonstrated that oxidative stress plays an important role in several ailments including neurodegenerative diseases and cerebral ischemic injury. Previously we synthesized some carbazole compounds that have anti-oxidant ability in vitro. In this present study, we found that one of these 22 carbazole compounds, compound 13 (3-ethoxy-1-hydroxy-8- methoxy-2-methylcarbazole-5-carbaldehyde), had the ability to protect neuro2a cells from hydrogen peroxide-induced cell death. It is well known that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Neuro2a cells were maintained and cultured, as previously described [28,29]. Dulbecco's Modified Eagle Medium (DMEM), fetal bovine serum (FBS), and antibiotics were purchased from Thermo Fisher Scientific (Waltham, MA, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Neuro2a cells were maintained and cultured, as previously described [28,29]. Dulbecco's Modified Eagle Medium (DMEM), fetal bovine serum (FBS), and antibiotics were purchased from Thermo Fisher Scientific (Waltham, MA, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…In addition, the same trend of increasing TUJ1+ cells as seen in neurospheres was observed, suggesting that infection may lead to interruption (or, at least, a delay) in TUJ1 to NF-200 progression. Neurite outgrowth has been evaluated in Neuro2a cells by other groups under different stimuli/treatments, and it has been reported that this process can be modulated by carbazole derivatives (Furukawa et al, 2019), miRNA (You et al, 2020), Mob proteins (Lin et al, 2011) and polyphenols, including Resveratrol and Apigenin (Namsi et al, 2018). Interestingly, Resveratrol has been shown to revert T. gondii -induced cytokine release and purinergic signaling imbalance in neural progenitor cells (Bottari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have been interested in the synthesis of heterocyclic compounds by constructing fused pyridine ring systems based on a thermal electrocyclization of an azahexatriene moiety [14,15]. It has been hoped that the development of compounds with enhanced biological activity would be possible using these natural products and their derivatives [16][17][18]. We have previously reported the total syntheses of indolo [3,2-c]quinoline (isocryptolepine) [19], azaanthracenones (kalasinamide, marcanine A, and geovanine) [20], imidazo [4',5':4,5]pyrido [2,3-b]indole (grossularine-1 and -2) [21,22], imidazo [4,5-b]pyridine (2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine and 2-amino-1,6-dimethylimidazo [4,5-b]pyridine) [23], and imidazo [4,5-c]quinoline (imiquimod) [24] based on the electrocyclization of 2-azahexatriene involving an isocyanate moiety as the key intermediate.…”
Section: Introductionmentioning
confidence: 99%